George P. Prigatano’s contributions to neuropsychological rehabilitation and clinical neuropsychology: A 50-year perspective - García-Molina, Alberto; Prigatano, George P. (Frontiers in Psychology, 2022)
In the 1970s and 1980s, a multitude of cognitive rehabilitation programs proliferated to facilitate recovery after brain injury. However only a few programs provided a framework for ameliorating disturbances in the cognitive, psychological, and interpersonal spheres of the brain-injured patient. Greatly influenced by Leonard Diller and Yehuda Ben-Yishay's ideas and methods, George P. Prigatano began, in early 1980, a holistic neuropsychological rehabilitation program at the Presbyterian Hospital in Oklahoma City (Oklahoma). The objective of this paper is to summarize the contributions of George P. Prigatano to neuropsychological rehabilitation and clinical neuropsychology during his 50th year of practice. The main body of the paper is structured in three sections. The first section briefly explains the history of neuropsychological rehabilitation in the 20th century and the emergence of holistic neuropsychological rehabilitation programs in the 1970s. The second section describes the contributions of George P. Prigatano to neuropsychological rehabilitation and clinical neuropsychology (written by AGM). In the third section, the second author (GPP) prepared an autobiographical statement, which attempts to summarize some of the personal and professional experiences which influenced his work. George P. Prigatano's contributions to neuropsychological rehabilitation and clinical neuropsychology are essential to understanding the therapeutic approaches currently used in the treatment of brain-injured patients.